2019
DOI: 10.1039/c9nj03956b
|View full text |Cite
|
Sign up to set email alerts
|

Ni–Cu/Al2O3 catalysts for the selective hydrogenation of acetylene: a study on catalytic performance and reaction mechanism

Abstract: Employing in situ DRIFTS spectra have successfully elucidated the reaction mechanism of Ni&Cu-NP/γ-Al2O3 catalyzed C2H2 semihydrogenation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The formation of ethylene on the Ni catalyst is evidenced by the characteristic peaks of the CH 2 scission and the C=C stretching vibration 45 at 1607 and 1709 cm −1 , respectively. In addition, the peaks at 2933 and 2968 cm −1 corresponded to the -CH 2 asymmetric stretching of long-chain hydrocarbons and -CH 3 asymmetric stretching of alkanes 46 , respectively, indicate the facile coupling and over-hydrogenation processes on the Ni catalyst. These are in good accordance with observed higher selectivities to ethane and C 4 components in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The formation of ethylene on the Ni catalyst is evidenced by the characteristic peaks of the CH 2 scission and the C=C stretching vibration 45 at 1607 and 1709 cm −1 , respectively. In addition, the peaks at 2933 and 2968 cm −1 corresponded to the -CH 2 asymmetric stretching of long-chain hydrocarbons and -CH 3 asymmetric stretching of alkanes 46 , respectively, indicate the facile coupling and over-hydrogenation processes on the Ni catalyst. These are in good accordance with observed higher selectivities to ethane and C 4 components in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Since VIII metals such as Pd and Ni are strong in ethyne activation and IB metal-based catalysts are selective for ethylene formation, VIII-IB bimetallic catalysts have been widely constructed to achieve high ethyne conversion and high selectivity towards ethylene simultaneously. Pd-Ag, 20,[101][102][103][104][105][106][107][108][109][110][111][112][113] Pd-Au, 114,115 Pd-Cu, [116][117][118] Ni-Cu, 119 Pt-Cu, 120 Ni-Ag, 121 and Ni-Au (ref. 122) have been developed.…”
Section: ① Viii-ib Catalystsmentioning
confidence: 99%
“…In general, Cu catalysts exhibited good hydrogenation activity at higher temperatures (4150 1C). 9,43,44 The marked difference between CuO(T120-R150) and Cu catalyst in hydrogenation activity might be related to the new crystal phase of Cu x C. [23][24][25] It was reported that, compared with the parent metals, interstitial metal carbides were more capable of adsorbing/activating H 2 and transferring active hydrogen to the reactant molecules. 45 Fig.…”
Section: Catalytic Performancementioning
confidence: 99%